SPEAKING DIFFICULTIES OF INTROVERT AND EXTRAVERT EFL STUDENTS: A PSYCHOLINGUISTIC ANALYSIS THROUGH LEVELT'S MODEL - Rezki Mawlani; Kalsum Kalsum; Zulfah Fakhruddin; Mujahidah (Tadulako University, 2026)
Speaking is a crucial yet challenging productive skill for English as a Foreign Language (EFL) learners because it demands the simultaneous processing of several linguistic components in real time. Beyond linguistic limitations, personality traits such as introversion and extraversion shape how learners cope with the cognitive and affective pressure of speaking. However, most existing studies compare speaking achievement scores rather than the internal processes through which speech is produced. This study investigates the speech disfluencies and speaking difficulties of introvert and extravert students from a psycholinguistic perspective by mapping them onto the stages of Levelt's Speech Production Model: conceptualization, formulation, and articulation. Using a qualitative descriptive-exploratory design, we involved 15 second-semester undergraduate students of Class A at IAIN Parepare, selected through purposive sampling based on the extraversion dimension of the Big Five Inventory. Data were gathered through a picture description task, a retrospective think-aloud protocol, and semi-structured interviews, then coded into six disfluency tokens and traced to specific production stages. The findings show that extravert learners lean toward communicative fluency, using filled pauses and spontaneous translanguaging as floor-holding strategies during formulation, whereas introvert learners prioritize accuracy through extended silent pauses, repetitions, and self-correction driven by intensive internal monitoring. The study contributes a stage-specific mapping of how personality modulates the internal mechanisms of L2 speech production at the tertiary level.